Penentuan Jarak Pendistribusian Gas LPG 3 Kg Dengan Metode Algoritma Heuristik - Sutoni, Akhmad; Asilah, Nur (Universitas Suryakancana, 2018)
PT. Anugrah Ditamas Lestari is an agent of 3 kg LPG Gas, to distribute to bases. PT. Anugrah Ditamas Lestari has a problem in distributing 3 kg of gas to the base, so it must have good planning so that the items to be distributed can reach the base in a timely manner. Traveling Salesman Problem (TSP) is a distribution problem in the form of transportation equipment (vehicle) from the agent to the base then back to PT. Anugrah Ditamas Lestari (agent). The research conducted aims to determine the minimum mileage for each route. The preparation of this Gas distribution route was completed using the Heuristic Algorithm. The initial stage is the formation of a sub route which is the process of grouping the base into the route. The next stage of the sub route development phase that has been formed is based on the existing travel time, the last stage minimizes the distance where the agent must first deliver the product until the last base and return to the agent. Sub route formation is still done manually while to compare the final results is done using WinQSB Software. Based on this distance determination study, the distance traveled was closer, and did not come to the base twice.